A comparative analysis of the coaching skills required by coaches operating in different non-competitive paddlesport settings. Issue 2 (2nd April 2020) - Sinfield, Dean; Allen, Justine; Collins, Loel
ABSTRACT: This paper examines the coaching behaviours of different paddlesport coaches (n = 17). A sample of coaches specialising in non-competitive paddlesport from professional, club and educational contexts are examined utilising a thematic analysis of semi-structured interviews. The three groups are shown to share common aspect such the importance of interpersonal skills within their coaching, the development of their coaching skill set via experiential learning and effective reflection and the importance of effective Professional Judgment and Decision making. However, the groups differ in respect to how they view their coaching role, the role of personal performance skills within their coaching and the impact of formal coach education in their development. The implication for coach education is that coaches working in an educational setting may be better served by a coach educational process that focusses more specifically on their skill set requirements and less on performance development.